The Influence of Social Media Engagement and Paylater Service on TikTok Shop Customer Loyalty in Bali - I Gusti Made Mahendradatta; Dwi Sih Winarti; Putu Astri Lestari (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Alongside the growing use of Buy Now Pay Later (Paylater) payment systems, social commerce platforms like TikTok Shop have expanded due to Indonesia's fast development of digital technology. The purpose of this study is to investigate the partial and simultaneous effects of Paylater services and social media involvement on customer loyalty among Bali TikTok Shop customers. A quantitative approach with a survey method was employed, using purposive sampling to collect data from 110 respondents who were active TikTok users, had made purchases through TikTok Shop, resided in Bali, and had used Paylater services. Data were analyzed using multiple linear regression with SPSS 27. The results show that social media engagement has a positive and significant effect on customer loyalty (t = 9.547, p < 0.001), and Paylater services also have a positive and significant effect on customer loyalty (t = 4.981, p < 0.001). Simultaneously, both variables significantly influence customer loyalty (F = 64.390, p < 0.001), with a coefficient of determination (R²) of 0.546, indicating that 54.6% of the variation in customer loyalty is explained by social media engagement and Paylater services, while the remaining 45.4% is explained by other factors outside the model. These findings confirm that stronger social media interaction and more convenient, flexible Paylater payment features jointly contribute to higher customer loyalty toward TikTok Shop in Bali. Keywords: Social media engagement, Paylater, customer loyalty, TikTok Shop, Bali